The Root of Halal Green in the Light of the Holy Quran and Sunnah Towards Sustainability and well Being: A Review - Deuraseh, Nurdeng; Matusin, Siti Nur Idayu Binti Haji; Hashim, Norkhairiah (Technium Social Sciences Journal, 2023)
There are teachings of Islam that are basically encouraging the Muslims to protect the planet or their surroundings. Every single person definitely can contribute and create impacts with their actions towards the environment; it may be good, but it may also be bad. As Muslims, it is part of their religious duties to make good impact towards the environment in general and to the earth in particular. This article is an attempt to review, study and evaluate green concept in the light of Quran and Sunnah that may contribute positively towards a healthy environment for human well being. It is found that, as khalifah on the earth, who has the responsibility to take good care of it as amanah of Allah s.w.t, he/she is responsible to bring Allah s.w.t creation back to natural state known as Green Earth/Halal Green.